2014
DOI: 10.2147/copd.s62502
|View full text |Cite
|
Sign up to set email alerts
|

Lung function efficacy and symptomatic benefit of olodaterol once daily delivered via Respimat® versus placebo and formoterol twice daily in patients with GOLD 2–4 COPD: results from two replicate 48-week studies

Abstract: Two replicate, multicenter, randomized, double-blind, placebo-controlled, parallel-group, Phase III studies investigated the long-term efficacy and safety of once-daily olodaterol via Respimat® versus placebo and formoterol over 48 weeks in patients with moderate to very severe chronic obstructive pulmonary disease receiving usual-care background therapy. Patients received once-daily olodaterol 5 or 10 μg, twice-daily formoterol 12 μg, or placebo. Co-primary end points were forced expiratory volume in 1 second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 30 publications
1
76
0
6
Order By: Relevance
“…Olodaterol is a novel once-daily long-acting b 2 -agonist (LABA) that is highly selective with nearly full intrinsic activity at b 2 receptors [7,8]. Phase III trials have demonstrated that olodaterol is effective at improving lung function over 24 h in patients with COPD [9e12] and, importantly, also provides improvements in patient-reported symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Olodaterol is a novel once-daily long-acting b 2 -agonist (LABA) that is highly selective with nearly full intrinsic activity at b 2 receptors [7,8]. Phase III trials have demonstrated that olodaterol is effective at improving lung function over 24 h in patients with COPD [9e12] and, importantly, also provides improvements in patient-reported symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…We recommend the use of an inhaled long-acting bronchodilator, either LAMA or LABA monotherapy, to reduce dyspnea, improve exercise tolerance, and improve health status in stable COPD patients 32,33,37,38,40,44,[49][50][51][52][53][54][55][56][57][58][59][60] (Grade 1A). 2.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Four phase III clinical studies (trials 1222.11 to 1222.14) of long-term efficacy and safety were used to support licensing applications in the USA and Europe 18–20. In addition, four studies examined the effect on 24-hour lung function over 6 weeks of treatment (trials 1222.24, 1222.25, 1222.39 and 1222.40) 13,21.…”
Section: About Olodaterolmentioning
confidence: 99%
“…The pivotal phase III randomised double-blind placebo-controlled parallel group studies compared olodaterol 5μg and 10μg with placebo19,20 and inhaled formoterol 12μg twice daily20 over 48 weeks. Although the prespecified primary outcome in each study was between olodaterol and placebo, the final sample size was based on the requirements for the comparison between olodaterol and formoterol.…”
Section: About Olodaterolmentioning
confidence: 99%
See 1 more Smart Citation